Personal exposure to concentrations and inhalation of black carbon according to transport mode use: The MobiliSense sensor-based study - Sanjeev Bista (Elsevier, 2022)
Introduction: Epidemiological evidence suggests that motorized vehicle users have a higher air pollutant exposure (especially from vehicle exhaust) than active (walking or cycling) transport users. However, studies often relied on insufficiently diverse sample and ignored that minute ventilation has an effect on individuals’ inhaled dose. This study examined commuters’ breathing zone concentration and inhaled doses of black carbon (BC) when travelling by different transport modes in the Grand Paris region. Methods: Personal exposure to BC was continuously measured with MicroAethalometer (MicroAeth AE51) portable monitors strapped on participants’ shoulder with tube inlet at the level of the neck (breathing zone), and inhaled doses were derived from several methods estimating ventilation [based on metabolic equivalents from accelerometry [METs], heart rate, and breathing rate]. Trip stages and transport modes were assessed from GPS and mobility survey data. Breathing zone concentrations and inhaled doses of BC were compared across transport modes at the trip stage level (n = 7495 for 283 participants) using linear mixed effect models with a random intercept at individual level. Results: Trip stages involving public transport and private motorized transport were associated with a 2.20 µg/m3 (95% CI: 1.99, 2.41) and 2.29 µg/m3 (95% CI: 2.10, 2.48) higher breathing zone concentration to BC than walking, respectively. Trip stages with other active modes had a 0.41 µg (95% CI: 0.25, 0.57) higher inhaled dose, while those involving public transport and private motorized transport had a 0.25 µg (95% CI: −0.35, −0.15) and 0.19 µg (95 %CI: −0.28, −0.10) lower inhaled dose of BC per 30 min than walking. Conclusion: The ranking of transport modes in terms of personal exposure was markedly different when breathing zone concentrations and inhaled doses were considered. Future studies should take both into account to explore the relationship of air pollutants in transport microenvironments with physiological response.